2015
DOI: 10.34024/rnc.2015.v23.7992
|View full text |Cite
|
Sign up to set email alerts
|

Influência do Conceito Bobath na função muscular da paralisia cerebral quadriplégica espástica

Abstract: Introdução. A Paralisia Cerebral (PC) é uma desordem que ocorre no Sistema Nervoso Central e interfere no funcionamento do sistema músculo esquelético. O conceito Bobath é baseado na neuroplasti­cidade e se utiliza da facilitação, normalização/adequação do tônus e reeducação do movimento, para auxiliar no desenvolvimento do movimento desejado. Objetivo. Avaliar a influência do Conceito Bobath na função muscular de um paciente com PC quadriplégica espástica. Método. Relato de caso sobre uma criança com PC qua­d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The Bobath application showed good results in other pathologies with similar motor disorders. The Bobath effectiveness in the study carried out by Firmino et al (2015) (10) was shown through surface electromyography (EMG) in a seven-year-old child with spastic quadriplegic cerebral palsy (CP), being possible to observe a higher activation of the paravertebral and internal oblique/transverse abdominal muscles in a single session, which provided an improvement in postural alignment at the end of treatment (8) . Another study, also carried out with children diagnosed with spastic CP, showed significant results in improving spasticity and gross motor learning after three months of rehabilitation with techniques based on the Bobath concept (11) .…”
mentioning
confidence: 99%
“…The Bobath application showed good results in other pathologies with similar motor disorders. The Bobath effectiveness in the study carried out by Firmino et al (2015) (10) was shown through surface electromyography (EMG) in a seven-year-old child with spastic quadriplegic cerebral palsy (CP), being possible to observe a higher activation of the paravertebral and internal oblique/transverse abdominal muscles in a single session, which provided an improvement in postural alignment at the end of treatment (8) . Another study, also carried out with children diagnosed with spastic CP, showed significant results in improving spasticity and gross motor learning after three months of rehabilitation with techniques based on the Bobath concept (11) .…”
mentioning
confidence: 99%